THE SEVEN INTERNATIONAL CONGRESSES OF ACCOUNTANTS. - Murphy, Mary E. (The Accounting Review, 1961)
Abstract The article assess the accomplishments of seven International Congresses of Accountants held to date. The first congress held in 1904 in St. Louis, Missouri sponsored by the Federation of Societies of Public Accountants in the U.S., must be attributed to George Wilkinson, an Illinois certified professional accountant (CPA) who was born in England, but spent his professional life in the U.S. The 1904 Congress was an ambitious event for the American accounting profession. It was held when The American Association of Public Accountants had a membership of only 140 scattered over 15 states, of whom 81 held CPA certificates. The Third International Congress was held in New York City in September 1929. Joseph E. Sterrett and F. van Dien, presidents of the earlier congress, served as Honorary Presidents, while Robert H. Montgomery held the role of President of the 1929 sessions. The 1952 Congress, convened in London, England, included about 80 CPAs from the United States. It exercised a constructive influence on international finance and commerce, and stimulated avid discussion and subsequent research on fluctuating price levels in relation to accounts, accounting requirements for issues of capital, the accountant in industry, the accountant in practice and in public service, and the incidence of taxation.